Meta Analisis Model Pembelajaran Inquiry untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Sanita, Risky; Anugraheni, Indri (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
The purpose of this study is to reanalyze the use of the Inquiry learning model to improve primary school student learning outcomes. This type of research was a meta-analysis. The research began with formulating a research problem, then testing the relevant research results for analysis. The data collection technique used non-test in the form of searching electronic journals through Google Scholar as well as documentation studies in libraries. The search results obtained 29 articles from journals and 3 theses articles from the repository. Based on the results of the analysis, it revealed that the Inquiry learning model was able to improve the student learning outcomes ranging from the lowest 1.4% to the highest 58.33% with an average of 20.88%. From the calculation of the effect size on the 29 articles and 3 theses analyzed, it was resulted that the effect size was 4.94 on average.